Development of healthy gummy jellies containing honey and propolis - Rivero, Roy Cristian (2019)
BACKGROUND: The objective of this work was to develop gummy jellies containing honey and propolis, keeping the natural antioxidant principles of the beehive ingredients and satisfying consumer requirements. RESULTS: A gummy jelly containing honey and propolis (HPGJ) was developed. A sensory study with consumers (n = 74) performed an intensity level evaluation test analyzing color, hardness, adhesiveness, gumminess, sweet taste and honey taste. A penalty analysis indicated that HPGJ was too hard. However, in the global acceptance study, more than 90% of consumers gave liking categories. Regarding the potential functional properties, the antioxidant capacity (AC) of HPGJ was 8.17 ± 0.55 mmol Trolox equivalent kg−1, and up to 40% AC was retained after in vitro digestion. Additionally, AC of HPGJ was up to ten times higher than that of similar commercial products. A storage study at 25 °C showed that color and AC increased significantly over 90 days owing to the development of Maillard reaction. Storage under darkness allowed keeping low values of global color change for up to 45 days. Another positive facet was that the addition of propolis delayed fungal growth during storage. CONCLUSION: An organoleptically palatable gummy jelly was obtained. Among the positive features, it showed higher AC than similar commercial candies. Additionally, HPGJ offered a high bioaccesible AC input detected upon in vitro digestion. Overall, HPGJ could be considered an interesting, appetizing and healthier alternative to regular gummy jellies available in the market. Adequate packaging should be considered in order to extend HPGJ shelf life, reducing browning reactions.